Validity and clinical utility of DSM and prototype diagnosis for depressive and anxiety spectrum disorders in predicting adaptive functioning. (December 2018) - Nakash, Ora; Nagar, Maayan; Bentov-Gofrit, Daphne; MD, Evelyne; Amiaz, Rvital; Lev-Ran, Shaul; Westen, Drew
Highlights: Prototype matching involves comparing a patient clinical presentation with a prototype description of the disorder. Most research to-date on prototype matching has been conducted with personality disorders. We tested the validity and clinical utility of prototype matching diagnosis for mood and anxiety disorders in a multi-method, multi informant study. Prototype diagnosis showed incremental validity above categorical DSM IV diagnosis in predicting patient's global adaptive functioning. Using a dimensional approach that is based on prototype matching offers a valid and efficient approach to psychiatric assessment. Abstract: Prototype matching, which involves comparing a patient clinical presentation with a prototype description of the disorder, addresses some of the clinical limitations of categorical approaches. Most research to-date on prototype matching has been conducted with personality disorders. Here, we examined the validity and clinical utility of prototype diagnosis for mood and anxiety disorders. We compared clinicians prototype diagnosis (based on DSM IV and empirically derived) to categorical diagnosis (based on independent SCID interview) in predicting patient global adaptive functioning rated across the clinician, patient and independent interviewer among N = 80 clinicians and N = 170 patients. Our findings show that prototype diagnosis (both one that is based on DSM criteria and empirically derived) demonstrates some incremental validity over and above the categorical DSM IV, in predicting patient's global adaptive functioning. This is particularly pronounced for mood disorders (MDD and dysthymia) as well as several anxiety disorders (OCD, social phobia) across a range of experience level of diagnosticians. Furthermore, clinicians rated the prototype matching approach as more useful in clinical practice compared with the binary categorical system. Using a dimensional approach, which is based on prototype matching that also preserves the advantages of categorical system offers a valid and efficient approach to psychiatric assessment.